Can double PPO mutations exist in the same allele and are such mutants functional?. Issue 6 (16th March 2022) - Porri, Aimone; Noguera, Matheus M; Betz, Michael; Sälinger, Daniel; Brändle, Frank; Bowe, Steven J; Lerchl, Jens; Meyer, Lucie; Knapp, Michael; Roma‐Burgos, Nilda
Abstract: BACKGROUND: Resistance to protoporphyrinogen oxidase (PPO)‐inhibiting herbicides is endowed primarily by target‐site mutations at the PPX2 gene that compromise binding of the herbicide to the catalytic domain. In Amaranthus spp. PPX2, the most prevalent target mutations are deletion of the G210 codon, and the R128G and G339A substitutions. These mutations strongly affect the dynamic of the PPO2 binding pocket, resulting in reduced affinity with the ligand. Here we investigated the likelihood of co‐occurrence of the most widespread target site mutations in the same PPX2 allele. RESULTS: Plants carrying R128G+/+ ΔG210+/−, where + indicates presence of the mutation, were crossed with each other. The PPX2 of the offspring was subjected to pyrosequencing and E. coli‐ based Sanger sequencing to determine mutation frequencies and allele co‐occurrence. The data show that R128G ΔG210 can occur in one allele only; the second allele carries only one mutation. Double mutation in both alleles is less likely because of significant loss of enzyme activity. The segregation of offspring populations derived from a cross between heterozygous plants carrying ΔG210 G399A also showed no co‐occurrence in the same allele. The offspring exhibited the expected mutation distribution patterns with few exceptions. CONCLUSIONS: Homozygous double‐mutants are not physiologically viable. Double‐mutant plants can only exist in a heterozygous state. Alternatively, if two mutations are detected in one plant, each mutation would occur in a separate allele. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Although the occurrence of two mutations in a same PPX2 allele is possible, Palmer amaranth plants carrying such allele must rely on the alternative allele to produce a functional enzyme.